The permaculture earthworks handbook : how to design and build swales, dams, ponds, and other water harvesting systems - Barnes, Douglas, 1969- (New Society Publishers, 2017)
"The Permaculture Earthworks Handbook covers the functions and appropriate siting, design, and construction of nine types of earthworks, including swales, dams, ponds, and hügelkultur beds, to maximize water availability in any climate. It's an essential practical guide for landscape designers, permaculturists, and landowners seeking to maximize food production and ecosystem resiliency at the lowest cost and impact."--